The answer is 56 hope this helps
Answer:
20
Step-by-step explanation:
So you want to solve for x?
It would be nice if this would easily factor:
(-4x + 5)(2x +1) = 0 This will not work!
So you need to use the quadratic formula:
a = -8, b = 4, c = 5
![x = \frac{-b+/- \sqrt{b^{2}-4ac} }{2a}](https://tex.z-dn.net/?f=%20%20x%20%3D%20%5Cfrac%7B-b%2B%2F-%20%20%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%20%7D%7B2a%7D)
x = (-4 +/-
![\sqrt{16-4(-8)(5)}](https://tex.z-dn.net/?f=%20%5Csqrt%7B16-4%28-8%29%285%29%7D%20)
)/2(-8)
= (-4 +/-
![\sqrt{16 + 160}](https://tex.z-dn.net/?f=%20%20%5Csqrt%7B16%20%2B%20160%7D%20%20)
)/-16
= (-4 +
![\sqrt{176}](https://tex.z-dn.net/?f=%20%5Csqrt%7B176%7D%20)
)/-16
= 1/4 -
![\sqrt{11}](https://tex.z-dn.net/?f=%20%5Csqrt%7B11%7D%20)
/4
Answer:
let x as a cointerior angle and find the
Answer:
Step-by-step explanation:
33